Implementation of CORDIC Algorithm in vectoring mode / Anis Shahida Mokhtar and Abdullah Mohd Fadzullah - Mokhtar, Anis Shahida; Mohd Fadzullah, Abdullah (2015)
Coordinate Rotation Digital Computer (CORDIC) is an algorithm for performing a sequence of iteration computing using the coordinate rotation. The significant of CORDIC lies in the fact that by simple shift-add operations, it can perform computing task such as the calculation of trigonometric, hyperbolic and logarithmic functions, real and complex multiplications, divisions, square roots and many others. In this paper, vectoring mode of CORDIC algorithm was implemented. The algorithm was developed using Verilog HDL in Quartus II software and the results obtained were compared with actual values of the CORDIC algorithm. The highest percentage of difference recorded between the actual value and simulation value was 2.65%.